Effect of Geometrical Confinement on Ordering of Thermoplastic Polyurethanes with Crystallizable Hard and Soft Blocks - Ainur F. Abukaev; Marina A. Gorbunova; Denis V. Anokhin; Dimitri A. Ivanov (Crystals, 2023)
A series of multi-block thermoplastic polyurethanes incorporating different soft block structures was synthesized. This was achieved using a poly(butylene adipate) oligomer combined with its macrodiols of both an aromatic and aliphatic nature. The composition of the hard block included 1,6-hexamethylene diisocyanate, 4,4′-diphenylmethane diisocyanate, and 1,4-butanediol. For the first time, the structural evolution and phase composition of both the hard and soft segments were analyzed during in situ thermal treatments. A combination of synchrotron small- and wide-angle X-ray scattering, differential scanning calorimetry, thermogravimetric analysis, and Fourier transform infrared spectroscopy was used to determine the influence of the macrodiol’s nature and crystallization conditions on the polymorphic behavior of poly(butylene adipate). Using a new synthesis scheme, a relatively high degree of crystallinity for urethane blocks was achieved, which depended on the diisocyanate type in the structure of the soft segment. The hard segment domains imposed geometrical constraints on poly(butylene adipate), thereby altering its crystallization process compared to the neat oligomer. Thus, crystallization after annealing at a low temperature (80 °C) was fast, predominantly yielding a metastable β-phase. When heated to 180 °C, which was higher than the hard segment’s melting temperature, a phase-separated structure was observed. Subsequent crystallization was slower, favoring the formation of the stable α-PBA modification. The phase separation could be observed even after the hard block melting. Notably slow crystallization from an isotropic melt was documented after the disruption of phase separation at 230 °C.